Predictors of Patient Dissatisfaction with Services for Prevention of Mother-To-Child Transmission of HIV in Dar es Salaam, Tanzania - Naburi, Helga (PLoS One, 2016)
BACKGROUND: Mother-to-child transmission (MTCT) of HIV remains a major source of new HIV infections in children. Prevention of mother-to-child transmission of HIV (PMTCT) using lifelong antiretroviral treatment (ART) for all pregnant and breastfeeding women living with HIV (Option B+) is the major strategy for eliminating paediatric HIV. Ensuring that patients are satisfied with PMTCT services is important for optimizing uptake, adherence and retention in treatment. METHODS: We conducted a facility based quantitative cross-sectional survey in Dar-es-Salaam, Tanzania, between March and April 2014, when the country was transitioning to the implementation of PMTCT Option B+. We interviewed 595 pregnant and breastfeeding women living with HIV, who received PMTCT care in 36 public health facilities. Predictors of overall dissatisfaction with PMTCT services were identified using a multiple logistic regression. RESULTS: Overall 8% of the patients expressed dissatisfaction with PMTCT services. Patients who perceived health care workers (HCW) communication skills as poor, had a 5-fold (OR 4.9, 95% CI 1.8–13.4) increased risk of dissatisfaction and those who perceived HCW capacity to understand client concerns as poor, had a 6-fold (OR 5.7, 95% CI 2.3–14.0) increased risk. Having a total visit time longer than two hours was associated with a 2-fold increased risk of being dissatisfied (OR 2.3, 95% CI 1.1–4.7). Every 30-minute increment in total visit time was associated with a 10% higher (OR 1.1, 95% CI 1.0–1.2) risk of being dissatisfied. The probability of being dissatisfied ranged from 4% (95% CI 2% - 6%) in the presence of patient-perceived good communication, good understanding of patient concerns, and a total visit time below two hours, to 70% (95% CI 47% - 86%) if HCW failed in all of these aspects. CONCLUSION: Patient dissatisfaction with PMTCT services was generally low; reflecting that quality of care was maintained during Tanzania’s transition to Option B+ strategy aiming to increase the number of women initiating life-long ART in PMTCT clinics. Improved HCW communication with clients, their understanding of patient concerns and a reduction of the total visit time would further optimize women’s overall satisfaction with PMTCT services in Tanzania.